The subject of anthropology : gender, symbolism and psychoanalysis. - Moore, Henrietta L. (Polity, 2007)
This new book draws on anthropology, feminism and psychoanalysis to develop an original and provocative theory of gender and of how we become sexed beings. Written not just for professional scholars and for students but for anyone with a serious interest in how gender and sexuality are conceptualised, experienced and imagined -- Présentation de l'éditeur.